2020
DOI: 10.1016/j.snb.2019.127357
|View full text |Cite
|
Sign up to set email alerts
|

Extruded phosphorescence based oxygen sensors for large-scale packaging applications

Abstract: Extruded phosphorescent O2-sensitive composite materials comprising cross-linked polystyrene-divinylbenzene (PS-DVB) microspheres impregnated with Ptbenzoporphyrin dye and dispersed in low-density polyethylene (LDPE) or polylactic acid (PLA) carrier polymer are described. The sensors produced by hot melt extrusion method are specifically tailored to large-scale packaging applications and nondestructive measurement of residual O2 in packaged food products. A panel of LDPE and PLA based sensor materials in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Molecular oxygen (O 2 ) is one of the most important chemical species for life on earth. Determination of O 2 has important implications for bio-medicinal, industrial, and environmental chemistry (Kelly et al, 2020). For food packaging, the shelf-life of prepacked food depends on O 2 level because it can promote the growth of fungi and microorganisms (Yousefi et al, 2019 13d).…”
Section: Quality Control For Food Packagingmentioning
confidence: 99%
“…Molecular oxygen (O 2 ) is one of the most important chemical species for life on earth. Determination of O 2 has important implications for bio-medicinal, industrial, and environmental chemistry (Kelly et al, 2020). For food packaging, the shelf-life of prepacked food depends on O 2 level because it can promote the growth of fungi and microorganisms (Yousefi et al, 2019 13d).…”
Section: Quality Control For Food Packagingmentioning
confidence: 99%
“…In the past decades, the use of polymer‐dye composites as a design platform of food sensors has attracted great interest, since this methodology is relatively easy to implement and scale‐up. [ 42,45–54 ] In general, this type of sensor could be fabricated through immobilization of dyes into a polymer matrix through either physical blending or covalent chemical bonding. Compared to covalent bonding, the physical blending often encounters the problem of dye leaching from the polymer matrix, which may lead to decreased sensing sensitivity and potential food contamination.…”
Section: Food Sensors Based On Polymer–dye Compositesmentioning
confidence: 99%
“…However, this feature and, more importantly, the simplicity and scalability of the method by which they are produced makes it likely that they will retail at a much lower price than their current commercial counterparts which, as others have noted, are 'difficult to manufacture'. 17 Other work carried out on the 3D printed O 2 sensitive dots showed that large batches, i.e. arrays, can be easily printed on one sheet of PET and that the reproducibility of such batches, in terms of O 2 sensitivity, within a batch (typically containing 9 indicator dots) and from batch to batch was >98.5%.…”
mentioning
confidence: 98%
“…As noted by others, this high cost is because of the complexity of manufacture which is 'slow and difficult to control and standardise'. 17 As a consequence, although commonly used in many different areas, especially for research and product development, O 2 optical indicator technology has not found widespread use in applications, such as in packaging, where they are likely to have significant impact but which would require their low-cost mass manufacture and subsequent large-scale utilisation. Indeed, Kelly et al, commenting on O 2 optical indicators, notes that in order 'to become viable in mass-scale packaging applications, indicator costs need to be reduced by at least ∼2 orders'.…”
mentioning
confidence: 99%
See 1 more Smart Citation